The Relationship Between Parental Attention and Indonesian Language Learning Outcomes Among Upper-Grade Elementary School Students - Andi Tenri Enceny Nur; Abd. Kadir; Sitti Rahmi (PT. Lontara Digitech Indonesia, 2025)
This study aims to describe parental attention, describe Indonesian language learning outcomes, and analyze the relationship between parental attention and Indonesian language learning outcomes among upper-grade students at SDN 209 Kajaolaliddong, Kecamatan Barebbo, Kabupaten Bone. This study used a quantitative approach with a correlational research design. The sample consisted of 42 upper-grade students from Grades IV, V, and VI, selected using saturated sampling because the total population was fewer than 100 students. Data were collected using a parental attention questionnaire, a multiplechoice Indonesian language learning outcome test, and documentation. The data were analyzed using descriptive statistical analysis and inferential statistical analysis with the assistance of IBM SPSS Statistics version 26. The results showed that parental attention was in the good category, with a mean score of 74.17. Students’ Indonesian language learning outcomes were also in the good category, with a mean score of 76.19. The reliability test showed that the parental attention questionnaire obtained a Cronbach’s Alpha value of 0.674, while the Indonesian language test obtained a Cronbach’s Alpha value of 0.697, indicating that both instruments were reliable. The Spearman correlation test showed that the r-count value was 0.928, which was higher than the r-table value of 0.312, with a significance value of 0.000 < 0.05. Therefore, the alternative hypothesis was accepted. These findings indicate that there is a very strong and significant positive relationship between parental attention and Indonesian language learning outcomes. Thus, the higher the parental attention received by students, the higher their Indonesian language learning outcomes tend to be.